1996
DOI: 10.1093/oxfordjournals.eurheartj.a014756
|View full text |Cite
|
Sign up to set email alerts
|

Progressive ECG changes in arrhythmogenic right ventricular disease Evidence foran evolving disease

Abstract: Electrocardiography results were used to assess diagnosis and evolution of arrhythmogenic right ventricular disease. The initial ECG presentation and long-term changes were analysed in 74 consecutive patients with symptomatic ventricular tachycardia and arrhythmogenic right ventricular disease. On first available tracings, a left axis deviation of the QRS was found in 18 patients. The QRS length in V1 was > or = 110 ms in 39 patients, an epsilon wave was present in 17, and a complete right bundle branch block … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 8 publications
3
50
1
2
Order By: Relevance
“…A history of syncope had no prognostic value, in contrast with the report of Blomström-Lundqvist et al 19 The rate of ECG abnormalities (60% of patients with RV abnormalities in the present study, and 68% in the study of Berder et al 22 ) is related to the extent of the disease at the time of the evaluation, and such abnormalities may appear during evolution of the disease. 26 In addition, we found no prognostic value of inducibility of SVT by EPS, the presence of which seems correlated with the prevalence of spontaneous SVT. 20,22 The same conclusion applies to the presence of late potentials at SA-ECG that have no predictive value for mortality.…”
Section: Le Guludec Et Alcontrasting
confidence: 62%
“…A history of syncope had no prognostic value, in contrast with the report of Blomström-Lundqvist et al 19 The rate of ECG abnormalities (60% of patients with RV abnormalities in the present study, and 68% in the study of Berder et al 22 ) is related to the extent of the disease at the time of the evaluation, and such abnormalities may appear during evolution of the disease. 26 In addition, we found no prognostic value of inducibility of SVT by EPS, the presence of which seems correlated with the prevalence of spontaneous SVT. 20,22 The same conclusion applies to the presence of late potentials at SA-ECG that have no predictive value for mortality.…”
Section: Le Guludec Et Alcontrasting
confidence: 62%
“…25 Previous groups have reported a prevalence rate between 4% and 42%. 5,8-10, 26 Early small-scale studies suggested that the presence of tricuspid regurgitation and atrial enlargement were associated with the development of atrial arrhythmias. A recent large-scale retrospective study has mainly confirmed those findings.…”
Section: Discussionmentioning
confidence: 99%
“…The disease manifests in adolescents or young adults with ventricular arrhythmias [305] while clinical presentation in children is rare or underreported. The initial presenting symptom may be syncope (29%) or cardiac arrest (7-23%) [306][307][308] .…”
Section: Causes and Clinical Findingsmentioning
confidence: 99%
“…The initial presenting symptom may be syncope (29%) or cardiac arrest (7-23%) [306][307][308] . Monomorphic ventricular tachycardia with left bundle branch block morphology is the most common (70-92%) arrhythmia observed in RVC, but these may vary from asymptomatic premature ventricular beats to poorly tolerated polymorphic ventricular tachycardia [305,307,309,310] . Like hypertrophic cardiomyopathy, RVC may lead to cardiac failure [308] , but it is more frequently associated with SCD [301,311,312] and if this can be prevented, life expectancy may be normal or near normal.…”
Section: Causes and Clinical Findingsmentioning
confidence: 99%
See 1 more Smart Citation